1997
DOI: 10.1175/1520-0450(1997)036<0428:fatdas>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Distribution and Spillover of Precipitation in the Southern Alps of New Zealand—A Case Study

Abstract: Rain gauge, radar, and atmospheric observations during a prolonged northwesterly storm in November 1994 have been used to study factors influencing the distribution of precipitation across the Southern Alps. Despite the persistent northwesterly flow, the location and intensity of precipitation varied markedly during this storm, providing an excellent dataset for these investigations. Data from 36 recording gauges in the northern half of the Alps were supplemented by data from 57 daily gauges, which were partit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
91
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 12 publications
(11 reference statements)
7
91
0
2
Order By: Relevance
“…Even with idealized topographic settings and flow configurations (e.g., isolated hill or ridge, constant flow), situations can be distinguished where precipitation maxima occur over the windward slope, the crest, or the downwind slope of a topographic obstacle (e.g., Sinclair et al, 1997;Smith, 1979). Distributions depend on the height and scale of the obstacle, and the strength, static stability and moisture profile of the impinging flow.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Even with idealized topographic settings and flow configurations (e.g., isolated hill or ridge, constant flow), situations can be distinguished where precipitation maxima occur over the windward slope, the crest, or the downwind slope of a topographic obstacle (e.g., Sinclair et al, 1997;Smith, 1979). Distributions depend on the height and scale of the obstacle, and the strength, static stability and moisture profile of the impinging flow.…”
Section: Introductionmentioning
confidence: 79%
“…Distributions depend on the height and scale of the obstacle, and the strength, static stability and moisture profile of the impinging flow. More complex topographic shapes, transient weather systems, convection, and the drift of hydrometeors quickly complicate the picture (e.g., Cosma et al, 2002;Fuhrer and Schär, 2005;Houze et al, 2001;Roe, 2005;Sinclair et al, 1997;Steiner et al, 2003). Therefore, the distribution of long-term mean precipitation is, in many regions, a superposition of several distinct responses to topography, which act at different space scales, involve several characteristics of the topography (not just height), and pertain to different flow situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Rapid generation of widespread rainfall, without the addition, the alpine rainfall process needed to explain why, delay required for standard autoconversion, was attributed to even in the statically unstable postfrontal environment lateral spreading of hydrometeors generated upwind of the [Sinclair et al, 1997], intense cells observed in the lowland foothills throughout the air mass. These hydrometeors could and foothills do not propagate to the alpine divide.…”
Section: Alpine Rainfall Processmentioning
confidence: 99%
“…For broader mountain ranges, the maximum rainfall tends to be positioned on the upstream side of the mountain (Rauber 1992), while the maximum in precipitation tends to be positioned more toward the mountain peak or lee slope for narrow mountains (Sinclair et al 1997). Colle (2004) studied the relationship between orographic precipitation distribution and environmental conditions and terrain geometry for a stable airstream impinging on a two-dimensional, idealized mountain.…”
mentioning
confidence: 99%